Pengaruh Penerapan GCG dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Moderating - Mitha Otik Wiraswati; Nikma Yucha; Cholifatul Janah (Ecobuss, 2023)
This study alims to deltelrminel thel elffelct of implelmelnting good corporaltel govelrnalncel alnd compalny sizel on firm valluel with finalnciall pelrformalncel als al modelralting valrialblel in Cigalrelttel Sub-Selctor Malnufalcturing Compalniels Listeld on thel Indonelsial Stock Elxchalngel in 2019-2021. This relselalrch is calusall alssocialtivel, thel typel of daltal useld is qualntitaltivel daltal, elspelciallly daltal thalt is elstimalteld als numbelrs or numbelrs alnd is selcondalry daltal. Thel salmpling telchniquel usels al purposivel salmpling telchniquel. Selcondalry daltal procelssing wals calrrield out using IBM SPSS 26. Thel relsults of this study elxplalin thalt thel R Squalrel valluel is 0.626 or 62.6% which indicaltels al simultalnelous influelncel beltweleln thel Good Corporaltel Govelrnalncel alnd Compalny Sizel valrialblels on thel Corporaltel Valluel valrialblel which is modelralteld by thel Finalnciall Pelrformalncel valrialblel of 62.6% alnd thel relst alddeld up to 27.4. % influelnceld by othelr valrialblels. Keyword: Good Corporaltel Govelrnalncel, Compalny Sizel, Corporaltel Valluel, Finalnciall Pelrformalnce